Synthesis and Textural Characterization of Mesoporous and Meso-/Macroporous Silica Monoliths Obtained by Spinodal Decomposition - Anne Galarneau (Inorganics, 2016)
Silica monoliths featuring either mesopores or flow-through macropores and mesopores in their skeleton are prepared by combining spinodal phase separation and sol-gel condensation. The macroporous network is first generated by phase separation in acidic medium in the presence of polyethyleneoxides while mesoporosity is engineered in a second step in alkaline medium, possibly in the presence of alkylammonium cations as surfactants. The mesoporous monoliths, also referred as aerogels, are obtained in the presence of alkylpolyethylene oxides in acidic medium without the use of supercritical drying. The impact of the experimental conditions on pore architecture of the monoliths regarding the shape, the ordering, the size and the connectivity of the mesopores is comprehensively discussed based on a critical appraisal of the different models used for textural analysis.